2015
DOI: 10.12688/f1000research.6923.1
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphic meta-analysis indicates early epigenetic outcomes & possible implications on genomic zygosity in type-2 diabetes

Abstract: Background: Dermatoglyphic studies, particularly those arising from the Dutch Hunger Winter Families Cohort, indicate an involvement of prenatal epigenetic insults in type-2 diabetes. However, the exact orchestration of this association is not fully understood. Herein is described a meta-analysis performed based on a belief that such an approach could shed some light as to the role of genetic & epigenetic influences in the etiology of type-2 diabetes. Methodology/principal findings: The study incorporated repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Dermatoglyphics has its fundamental basis in this premise, being an epigenetic marker related to the period of fetal development ( Yohannes, 2015 ). In addition to the fact that the fingerprints are intrinsically related to the central nervous system and can therefore reflect motor capacities inherited genetically and epigenetically for conditions that may have a marker expressed during this period of fetal development, fingerprint evaluation is a simple and practical method ( King et al ., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dermatoglyphics has its fundamental basis in this premise, being an epigenetic marker related to the period of fetal development ( Yohannes, 2015 ). In addition to the fact that the fingerprints are intrinsically related to the central nervous system and can therefore reflect motor capacities inherited genetically and epigenetically for conditions that may have a marker expressed during this period of fetal development, fingerprint evaluation is a simple and practical method ( King et al ., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the association between DGFs and health is the influence of epigenetics, which affects both ( Yohannes, 2015 ). The formation of the former begins in the first trimester of pregnancy, during the 6th week, is completed after the 24th week of gestation and is formed according to the development and maturation of the central nervous system ( Babler, 1991 ; King et al ., 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…25 Furthermore, numerous studies were also conducted in Ethiopia using various samplesrisk factors and clinical variables. For instance, the physical and medical risk factor of diabetes was studied by, T/Kiros et al, 26 Abebe et al, 13 Gebreyohannes et al, 27 Zekewos et al, 28 Yohanes, 29 and Alemu, 30 in another word, psychological disorder related to diabetes are forgotten.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Dermatoglyphics has its fundamental basis in this premise, since it is an epigenetic marker associated with the period of fetal development [ 37 ]. In the present study, the analysis of the association between BMI, fingerprints and gestational data showed no significant results; however, it was observed that the older the woman when she became pregnant, the greater the number of ridges on the child’s left index and right thumb.…”
Section: Discussionmentioning
confidence: 99%